1985
DOI: 10.1007/bf00384948
|View full text |Cite
|
Sign up to set email alerts
|

Higher survival of an aposematic than of a cryptic form of a distasteful bug

Abstract: An experiment was performed to assess the relative survival of two forms of 5th instar larvae of Lygaeus equestris (Heteroptera, Lygaeidae) - the normal red form, called aposematic, and a mutant grey form, called cryptic - when given to hand-raised great tits (Parus major).Sixteen birds were presented with aposematic larvae and 16 were presented with cryptic larvae in 10 consecutive trials. One attack per trial was allowed. Both larval forms were presented against a background matching the grey larvae, but sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
141
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(152 citation statements)
references
References 17 publications
9
141
2
Order By: Relevance
“…In support, Sillén-Tullberg (1985) found that the red forms of a distasteful Lygaeus bug survived a far greater proportion of attacks by naive great tits (Parus major) than more cryptic forms, and suggested that the conspicuously coloured larvae 'survived better because they were handled more cautiously by the birds' (p. 413). Indeed, this same study found that the conspicuous morph had a better overall chance of surviving than its cryptic conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…In support, Sillén-Tullberg (1985) found that the red forms of a distasteful Lygaeus bug survived a far greater proportion of attacks by naive great tits (Parus major) than more cryptic forms, and suggested that the conspicuously coloured larvae 'survived better because they were handled more cautiously by the birds' (p. 413). Indeed, this same study found that the conspicuous morph had a better overall chance of surviving than its cryptic conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, experimental studies of aposematism and mimicry have focused primarily on systems involving brightly patterned, conspicuous models. Predators learn to avoid brightly patterned or otherwise conspicuous noxious prey items more rapidly than cryptic prey items (Gittleman & Harvey 1980;Sillén-Tullberg 1985;Guilford 1986;Rowe & Guilford 2000), and consequently, aposematism and/or Batesian mimicry have usually been inferred in cases where the presumed mimic matches a brightly patterned model.…”
Section: Introductionmentioning
confidence: 99%
“…However, where generalist predators operate under similar sensory modalities as either prey or specialized predators, a potential alternative strategy would consist of the use of patterns and colours that do not interfere with crypsis, but are characteristically distinct and easily recognizable when crypsis has failed and the animal is spotted by a generalist predator. Although bright colours and patterns may enhance predator learning, experiments using captive birds have demonstrated that cryptic, noxious prey also gains protection against attack, albeit more slowly than conspicuous prey (Sillén-Tullberg 1985). Fisher (1930) emphasized the primary importance of recognizability for any noxious organism, and Mallet & Joron (1999) argued that any pattern could potentially generate predator avoidance provided it is recognizable and memorable, even if no conspicuous coloration is involved.…”
Section: Introductionmentioning
confidence: 99%
“…Aposematic coloration is the use of contrasting colors to warn predators of distasteful prey (Cott 1940). Even though brightly colored animals advertise their presence to potential predators, experimental evidence shows that contrasting color patterns can protect some insects better than cryptic color patterns (Sillen-Tullberg 1985). Most experimental studies have focused on terrestrial animals such as insects and snakes, in which contrasting color patterns deterred bird predators (Smith 1977, Sillen-Tullberg 1985, Lindstrom et al 1999) and some terrestrial invertebrate predators such as praying mantis and dragonflies (Bowdish & Bultman 1993, Kauppinen & Mappes 2003.…”
Section: Introductionmentioning
confidence: 99%
“…An ecological trait that confers a selective advantage for survival such as aposematic coloration (Sillen-Tullberg 1985) should be effective in both terrestrial and marine systems, but there is a lack of experimental evidence on the variety of visual predators that respond to aposematic signals (Mappes et al 2005). In addition, recent work with multiple terrestrial animals including monkeys, birds, and insects has shown that multiple cues presented together (termed multimodal cues) are more effective in communication than any 1 cue alone (Partan & Marler 1999).…”
Section: Introductionmentioning
confidence: 99%